2023
DOI: 10.3390/electronics12061361
|View full text |Cite
|
Sign up to set email alerts
|

Application of Numerical Simulation Technology in New Intelligent Reinforcing Method of Shield Tunnel End in Seaside Environment

Abstract: The instability of the soil at the shield end is an important safety hazard in shield tunnel construction. In loose and weak strata, the risk of instability and damage is higher, and the loss is greater. In this paper, the instability and failure of the end soil in loose and weak strata are studied. To ensure the smooth start and arrival of the shield and avoid engineering accidents such as end soil instability, surface subsidence, landslides, etc., during the construction process, this paper summarizes the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It was shown that the vertical displacement of the tunnels was significantly affected by the soil properties. Zeng et al [23] focused on the endings of shield tunnels and investigated the instability and damage of end soils in loose and weak strata and, using numerical simulation, the authors found that the reinforcement effect increases with the increase in thickness of the added solid, but the change rate becomes smaller and smaller. To investigate the shutdown problem of shield tunneling machines, Hasanpour et al [24] utilized finite-difference software to simulate the excavation process in unfavorable strata, and the results help to realistically assess the effect of unfavorable geological conditions on shield blockage.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the vertical displacement of the tunnels was significantly affected by the soil properties. Zeng et al [23] focused on the endings of shield tunnels and investigated the instability and damage of end soils in loose and weak strata and, using numerical simulation, the authors found that the reinforcement effect increases with the increase in thickness of the added solid, but the change rate becomes smaller and smaller. To investigate the shutdown problem of shield tunneling machines, Hasanpour et al [24] utilized finite-difference software to simulate the excavation process in unfavorable strata, and the results help to realistically assess the effect of unfavorable geological conditions on shield blockage.…”
Section: Introductionmentioning
confidence: 99%